Kecemasan ibu hamil trimester III menghadapi proses persalinan dan melahirkan - Ratna Dewi; Noviyanti Noviyanti; Adri Idiana (Holistik Jurnal Kesehatan, 2022)
Background: A pregnant woman will experience a period of labor and this is a critical period. It is not uncommon for mothers to have disturbing thoughts. The emergence of disturbing thoughts is related to the delivery process that will be passed and the form of thought that is felt is anxiety. Anxiety is a form of emotional response felt by pregnant women. This response is an anticipation of an experience that the patient perceives as threatening his or her role in life, the integrity of the body or life itself.Purpose: To determine the level of anxiety in third trimester pregnant women at PMB in the Working Area of the Ingin Jaya Health Center.Method: This research is descriptive to see the level of anxiety in third trimester primigravida pregnant women. The population in this study were pregnant women who were in PKM Ingin Jaya, totaling 50 respondents who met the inclusion and exclusion criteria. The instrument used in this study was an observation sheet about anxiety using the HARS questionnaire, <14: no anxiety, 14-20: mild anxiety, 21-27: moderate anxiety, 28-41: very severe anxiety.Results: Based on the table above shows that aged 25-35 years with moderate anxiety 15 (12.3%) respondents with p-value 0.017, high school education with moderate anxiety level 14 (13.4%) respondents with p-value 0.017, parity 1-2 people 20 (15.7%) respondents, with a p-value of 0.030.Conclusion: There is a significant relationship between parity, age, education on the anxiety level of third trimester pregnant women in facing childbirth.Keywords: Anxiety; Third trimester; Primigravida; Pregnant women; Labor and deliveryPendahuluan: Seorang ibu hamil akan mengalami masa persalinan dan ini merupakan salah satu periode kritis. Tidak jarang ibu memiliki pikiran yang mengganggu. Munculnya pikiran yang mengganggu itu terkait dengan proses persalinan yang akan dilalui dan bentuk pikiran yang dirasakan adalah kecemasan. Kecemasan merupakan sebuah bentuk respon emosional yang dirasakan oleh ibu hamil. Respon ini merupakan antisipasi terhadap pengalaman yang pasien anggap mengancam perannya dalam kehidupan, integritas terhadap tubuh atau kehidupan itu sendiri .Tujuan: Untuk mengetahui tingkat kecemasan pada ibu hamil trimester III di PMB Wilayah Kerja Puskesmas Ingin Jaya.Metode: Penelitian ini bersifat deskripsi  untuk melihat tingkat kecemasan pada ibu hamil primigravida trimester ketiga. Populasi dalam penelitian ini yaitu Ibu Hamil yang berada di PKM Ingin Jaya, yang berjumlah 50 orang yang  memenuhi kriteria inklusi dan eklusi. Instrumen yang digunakan dalam penelitian ini adalah lembar observasi tentang kecemasan dengan menggunakan kuesioner HARS, <14: tdk ada kecamasan,14-20: kecemasan ringan,21-27:kecemasan sedang,28-41: kecemasan berat sekali.Hasil: Berdasarkan tabel diatas menunjukkan bahwa usia 25-35 tahun dengan kecemasan sedang 15 (12.3%) responden dengan p-value 0.017, pendidikan SMA dengan tingkat kecemasan sedang 14 (13.4%) responden denagn p-value 0.017, paritas 1-2 orang 20 (15.7%) responden, dengan p-value 0.030.Simpulan: Terdapat hubungan yang bermakna antara Paritas, Umur, Pendidikan terhadap tingkat kecemasan Ibu Hamil Trimester III dalma menghadapi persalinan.